Gender inequality in the labor market: the principle of equality for the realization of the principle of non- discrimination against women - Lima, L. R. Rita; Moraes, S. F. S. Félix; Nodari, T. M. S. Maria (Scientific Electronic Archives, 2016)
The gender inequality has been present throughout human history, where the role of women in the family environment overtopped their occupation in other sectors. The discrimination and the culture of factors hinder the participation of women in equal or higher level of men in the labor market, however women have higher levels of study than men, which proves the inequality suffered by this genre. Currently, we have taken advances on the world stage, with women placed in new environments, as well as greater access to command positions in companies. We still need many advances for the men and women be treated in the same way how predict the laws. In this study we sought to analyze and discuss the role and the current position of woman in the labor market and in other spheres.